An Ultrasensitive Non-Enzymatic Sensor for Quantitation of Anti-Cancer Substance Chicoric Acid Based on Bimetallic Nanoalloy with Polyetherimide-Capped Reduced Graphene Oxide - Jiao, Jun (Nanomaterials (Basel), 2020)
Exploiting effective therapies to fight tumor growth is an important part of modern cancer research. The anti-cancer activities of many plant-derived substances are well known, in part because the substances are often extensively distributed. Chicoric acid, a phenolic compound widely distributed in many plants, has drawn widespread attention in recent years because of its extraordinary anti-cancer activities. However, traditional methods for quantifying chicoric acid are inefficient and time-consuming. In this study, an ultrasensitive non-enzymatic sensor for the determination of chicoric acid was developed based on the use of an Au@Pt-polyetherimide-reduced graphene oxide (PEI-RGO) nanohybrid-modified glassy carbon electrode. Owing to the considerable conductivity of PEI-functionalized RGO and the efficient electrocatalytic activity of Au@Pt nanoalloys, the designed sensor exhibited a high capacity for chicoric acid measurement, with a low detection limit of 4.8 nM (signal-to-noise ratio of 3) and a broad linear range of four orders of magnitude. With the advantages provided by the synergistic effects of Au@Pt nanocomposites and PEI-RGO, the developed sensor also revealed exceptional electrochemical characteristics, including superior sensitivity, fast response, acceptable long-term stability, and favorable selectivity. This work provides a powerful new platform for the highly accurate measurement of chicoric acid quantities, facilitating further research into its potential as a cancer treatment.